FGF20‐FGFR1 signaling through MAPK and PI3K controls sensory progenitor differentiation in the organ of Corti. Issue 2 (9th September 2020) - Su, Yutao; Yang, Lu M.; Ornitz, David M.
Abstract: Background: Fibroblast Growth Factor 20 (FGF20)‐FGF receptor 1 (FGFR1) signaling is essential for cochlear hair cell (HC) and supporting cell (SC) differentiation. In other organ systems, FGFR1 signals through several intracellular pathways including MAPK (ERK), PI3K, phospholipase C ɣ (PLCɣ), and p38. Previous studies implicated MAPK and PI3K pathways in HC and SC development. We hypothesized that one or both would be important downstream mediators of FGF20‐FGFR1 signaling for HC differentiation. Results: By inhibiting pathways downstream of FGFR1 in cochlea explant cultures, we established that both MAPK and PI3K pathways are required for HC differentiation while PLCɣ and p38 pathways are not. Examining the canonical PI3K pathway, we found that while AKT is necessary for HC differentiation, it is not sufficient to rescue the Fgf20 −/− phenotype. To determine whether PI3K functions downstream of FGF20, we inhibited Phosphatase and Tensin Homolog (PTEN) in Fgf20 −/− explants. Overactivation of PI3K resulted in a partial rescue of the Fgf20 −/− phenotype, demonstrating a requirement for PI3K downstream of FGF20. Consistent with a requirement for the MAPK pathway for FGF20‐regulated HC differentiation, we show that treating Fgf20 −/− explants with FGF9 increased levels of dpERK. Conclusions: Together, these data provide evidence that both MAPK and PI3K are important downstream mediators of FGF20‐FGFR1 signaling during HC and SC differentiation. Key Findings: PI3K and MEK1/2 are necessary for hair cell differentiation while p38 and PLCγ are not. pAKT is necessary but not sufficient for hair cell differentiation. PTEN inhibition partially rescues Fgf20 knockout phenotype. dpERK is downstream of FGF20‐FGFR1 signaling.